Ownership structure, independent board members and innovation performance: A contingency perspective - Chen, Chung-Jen; Lin, Bou-Wen; Lin, Ya-Hui; Hsiao, Yung-Chang (Journal of business research, 2016)
This study advances the research on corporate governance and innovation by investigating how technology diversity strategy and absorptive capacity shape the relationships between foreign ownership, independent board members and firm innovation in emerging economics. Using panel data from 138 Taiwanese firms, this study finds that the relationship between foreign ownership and innovation performance is negatively moderated by technology diversity strategy. The relationship between the proportion of independent board members on the board and innovation performance is positively moderated by technology diversity strategy, whereas the focal link is negatively moderated by absorptive capacity. These findings contribute to a better understanding of how the fit relationships of governance arrangements (foreign ownership and independent board members) with internal conditions (technology diversity strategy and absorptive capacity) influence firms' ability to benefit from innovation activities. Finally, this study discusses the managerial implications and highlights future research directions.